Demystifying the Salt-Induced Li Loss: A Universal Procedure for the Electrolyte Design of Lithium-Metal Batteries - Zhu, Zhenglu; Li, Xiaohui; Qi, Xiaoqun; Ji, Jie; Ji, Yongsheng; Jiang, Ruining; Liang, Chaofan; Yang, Dan; Yang, Ze; Qie, Long; Huang, Yunhui (Nano-Micro Letters, 2023)
Lithium (Li) metal electrodes show significantly different reversibility in the electrolytes with different salts. However, the understanding on how the salts impact on the Li loss remains unclear. Herein, using the electrolytes with different salts (e.g., lithium hexafluorophosphate (LiPF6), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(fluorosulfonyl)amide (LiFSI)) as examples, we decouple the irreversible Li loss (SEI Li+ and “dead” Li) during cycling. It is found that the accumulation of both SEI Li+ and “dead” Li may be responsible to the irreversible Li loss for the Li metal in the electrolyte with LiPF6 salt. While for the electrolytes with LiDFOB and LiFSI salts, the accumulation of “dead” Li predominates the Li loss. We also demonstrate that lithium nitrate and fluoroethylene carbonate additives could, respectively, function as the “dead” Li and SEI Li+ inhibitors. Inspired by the above understandings, we propose a universal procedure for the electrolyte design of Li metal batteries (LMBs): (i) decouple and find the main reason for the irreversible Li loss; (ii) add the corresponding electrolyte additive. With such a Li-loss-targeted strategy, the Li reversibility was significantly enhanced in the electrolytes with 1,2-dimethoxyethane, triethyl phosphate, and tetrahydrofuran solvents. Our strategy may broaden the scope of electrolyte design toward practical LMBs. Highlights: 1 The loss mechanisms of irreversible Li in electrolytes with various salts (e.g., lithium hexafluorophosphate (LiPF6), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(fluorosulfonyl)amide (LiFSI)) are systemically revealed. 2 A universal procedure for the electrolyte design of Li metal batteries is proposed: (i) decouple and find the main reason for the irreversible Li loss; (ii) add the corresponding electrolyte additive.